2014
DOI: 10.11648/j.jps.20140204.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sorghum (Sorghum bicolor (L.) Moench) Varieties, for Yield and Yield Components at Kako, Southern Ethiopia

Abstract: Abstract:A field experiment involving seven improved sorghum [Sorghum bicolor (L.) Moench] varieties and one local check was carried out at Kako farmers' training center during the 2006 main cropping season to identify the best performing variety to the lowlands of South Omo Zone. The sorghum varieties included in the field experiment were seven improved (Seredo, Meko-1, 76TI#23, Gambella 1107, Teshale, Gubiye, Abshir) and a local check. The experimental design was a randomized complete block design (RCBD) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…The shoot count in this study was in agreement with Yoseph and Sorsa (2014) who reported counts of 3, 2.8, and 2.7 for three improved sorghum varieties at flowering growth stage. There was a significant accretion in number of shoots from PS2 to PS3 with no significant accretion thereafter.…”
Section: Discussionsupporting
confidence: 92%
“…The shoot count in this study was in agreement with Yoseph and Sorsa (2014) who reported counts of 3, 2.8, and 2.7 for three improved sorghum varieties at flowering growth stage. There was a significant accretion in number of shoots from PS2 to PS3 with no significant accretion thereafter.…”
Section: Discussionsupporting
confidence: 92%
“…This was confirmed by the existing correlation between growing season rainfall and annual actual yield of the region for the period 2003-17. The increase in actual yield could be the result of change in the adoption of improved agronomic measures in the region during the stated period although it is found at its early stage (Shiferaw and Yoseph, 2014;Yoseph and Sorsa, 2014). Higher inter-annual variability of Melkam and Teshale Y w was observed at Benatsemay than Jinka for both models and this could be attributed to differences in edaphic and climatic conditions of the area.…”
Section: Yield Levels Variability and Gapsmentioning
confidence: 92%
“…In response to this Jinka agricultural research center has conducted sorghum varieties and agronomic management experiments at Nyangatom and Dasenech woreda of the south Omo zone (2019 and 2020) cropping seasons and Melkam sorghum variety and its agronomic management which gave higher yield (3.3 t•ha -1 to 5.4 t•ha -1 ) were recommended for further production in the area. And other previous works by different scholars (Tekle and Zemach [4] ; Fuad et al [5] ; Abebe et al, [6] ; Melese [7] ) focused on performance evaluation of sorghum varieties in arid and semiarid areas to enhance productivity. However, less emphasis has been given to commercializing sorghum production as compared to other cash crops like cotton and banana.…”
Section: Introductionmentioning
confidence: 99%